Visite au Tombeau du Grand Frédéric - Motte, Charles Etienne Pierre, 1785-1836 (lithographer):::Creator::::::::::::; Ponce-Camus, Marie Nicolas, 1778-1839 (artist):::Contributor::::::::::::; Levilly (artist):::Contributor:::::::::::: (Chez Émile Babeuf; France; Paris)
Lithograph of Napoleon visiting the tomb of Friedrich II of Prussia, part of a series of prints by Charles Motte depicting the life of Napoleon.